Predictors of pediatric surgeons' career satisfaction: a national survey. Issue 3 (July 2016) - Višnjić, Stjepan; Župančić, Božidar; Žganjer, Mirko
Abstract : Objective: A survey was performed to identify factors for professional career satisfaction and for dissatisfaction. Methods: During General Assembly of CSPS, attendees answered the 37-question form grouped into the following categories: demographic, professional activity and organizational issues, type of service, education, and compensation and status. Data were analyzed using the Pearson χ 2 test ( P <0.05). Results: The response rate was 74.5% ( n =44/59). The average age was 46 years, and 91% were male. The average participant had 17 years of surgical practice, worked 8.5 hours daily and 208 hours monthly, in children's (49%), university (35%), or community (16%) hospital. Pediatric surgeons were satisfied with professional career (77%), and 88% would chose the same profession again. Patient satisfaction (85%), quality of care (79%), and professional achievements (76%) were rated very high. Dissatisfaction responders pointed at shortage of time for effective communication (69%), excessive administrative work (88%), too many working hours (73%), professional burnout (66%), and technical issues – IT technology (73%) and equipment (79%) out of date or old/unsuitable facilities (73%). An overall 57% of responders had presented paper on international congresses, and 32% had published paper in indexed journals. Two major concerns about education are insufficient training (61%) and lack of time for continuous education (79%). Conclusion: Pediatric surgeons are satisfied with professional career. Patient care is a leading area of satisfaction. Educational, organizational, technical, and structural issues need improvements. A large pay gap exists between expectations and real income.